32 Testosterone Replacement Therapy (TRT) is not Associated with a Higher Risk of DVT: Retrospective Analysis of US Claims Data. Issue 1 (1st April 2022) - Hernandez-Vegas, E; Hotaling, J; Son, L; Horns, J; Paudel, N; Gross, K; Pastuszak, A; Patel, D
ABSTRACT: Introduction: As the prevalence of male hypogonadism (HG) has increased, more patients are prescribed TRT. TRT may be associated with an increased risk of deep venous thrombosis (DVT). Although in recent years there have been more studies dedicated to adverse effects of TRT, the literature is mixed on whether TRT increases the risk of DVT. Objective: This study evaluates the risk of developing DVT in men with hypogonadism based on which types of treatments trends they receive using the MarketScan insurance claims database. Methods: We performed a retrospective analysis of the IBM MarketScan™ Commercial Claims and Encounters database between 2008-2017. We identified all men with an HG diagnosis using the International Classification of Disease 9th edition (ICD-9) or 10th edition (ICD-10). We recorded how often they received TRT (including formulations as oral, topical/transdermal gels/creams/patches, intranasal, injections, and pellet implants). We followed men to see how many were diagnosed with DVT or pulmonary embolism. We excluded men who had a record of thromboembolic events before their first HG diagnosis. We performed univariate tests of variation across different demographics in three separate stratifications: 1) In all patients stratified by whether they suffered DVT; 2) In patients with DVT stratified by whether they received any kind of treatment at any time; 3) In patients with DVT and any treatment stratified by the type of treatment. Hazard Ratios from Cox Models were calculated for the effects of TRT in the previous 6 months on DVT controlling for the following confounding variables: age and comorbidities such as smoking, drug abuse, obesity, heart disease, cardiovascular problems and surgery/immobilization. Age and TRT in the previous 6 months were included as time-varying covariates. Results: We identified 1, 853, 889 total men with HG, of which 21, 414 (1.16%) were diagnosed with DVT. Among men who suffered DVT, 7, 487 (34.96%) received TRT at some point compared to 605, 534 (33.04%) of the men who did not suffer DVT. Results from time-varying Cox models suggest that receipt of TRT in the previous 6 months does not significantly increase the risk of developing a DVT (hazard ratio (HR) 1.049; 95% CI: 0.85, 1.29) among men with HG. Conclusions: Our study suggests that TRT is not associated with a higher risk of developing DVT. DVT has evidence that the association was more pronounced among patients of later middle age and with chronic disease, whether with or without TRT. Further investigation is warranted to assess the risk effect of TRT on DVT development, which may allow for a more proactive approach in management. Disclosure: No